Analisis Sistem Temu Balik Sertifikat Pendidik Menggunakan Metode Cosine Similarity - Rangga Wahyu Dealova; Deo Pradana; Ali Akbar Ramadhan; Safrizal Safrizal (International Forum of Researchers and Lecturers, 2026)
Educator certificates are official documents that play a crucial role for teachers, as they serve as legal proof of professional competence and are required for various administrative purposes, such as professional allowance applications, promotion, transfer, and institutional accreditation. Along with the increasing number of educators in Indonesia, the volume of educator certificate data managed by educational institutions has also grown significantly. However, certificate management is still largely conducted in a conventional manner, functioning merely as digital or physical archives without an effective search mechanism, resulting in inefficiencies and difficulties in retrieving relevant documents. Therefore, an information retrieval approach is needed to support fast and accurate document searching. This study aims to analyze and implement an information retrieval system for educator certificates using the Cosine Similarity method. The research data consist of educator certificate documents, including professional educator certificates, training certificates, and competency certificates. The retrieval process involves text preprocessing, term weighting using TF-IDF, and similarity measurement using Cosine Similarity. The results show that document d1 (Professional Mathematics Educator Certificate) has the highest similarity value to the query “educator certificate,” as it contains all query terms with relatively high TF-IDF weights. Document d3 ranks second due to partial term similarity, while document d2 has the lowest similarity value because it shares only one common term with the query. These findings indicate that the Cosine Similarity method is effective in ranking educator certificate documents based on their content relevance in an objective and measurable manner. The proposed system can improve the efficiency and accuracy of educator certificate document management and retrieval in educational institutions.